1990
DOI: 10.1002/aoc.590040105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the activity of some water‐soluble ferrocene and ferricenium compounds against carcinoma of the lung by the human tumor clonogenic assay

Abstract: The two ferrocene compounds, ferrocenylacetic acid (3) and ferrocylthiomalic acid (4), as well as the ferricenium salts, ferricenium tetrachloroferrate (111) (1) and ferricenium trichloroacetatetrichloroacetic acid solvate (2), were investigated by the in vitro human tumor clonogenic assay for their inhibiting effects, in continuous exposure in a double-layer medium, on the colony formation of single-cell suspensions prepared from 30 selected fresh specimens of human adenocarcinoma, squamous cell carcinoma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…11,13,14 Furthermore, collaborative testing programs were initiated with biomedical research groups, in which a number of ferricenium and ferrocene compounds were screeened for activity against ascitic murine tumors 18-20 and human clonogenic cancer lines. 21 The findings, demonstrating the need for solubility in aqueous media as a means of rapid distribution in central circulation, showed lack of activity for water-insoluble ferricenium salts but a high degree of activity for a number of readily soluble ferricenium salts, cure rates in two instances attaining the 100% level against Ehrlich ascites.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…11,13,14 Furthermore, collaborative testing programs were initiated with biomedical research groups, in which a number of ferricenium and ferrocene compounds were screeened for activity against ascitic murine tumors 18-20 and human clonogenic cancer lines. 21 The findings, demonstrating the need for solubility in aqueous media as a means of rapid distribution in central circulation, showed lack of activity for water-insoluble ferricenium salts but a high degree of activity for a number of readily soluble ferricenium salts, cure rates in two instances attaining the 100% level against Ehrlich ascites.…”
Section: Introductionmentioning
confidence: 96%
“…Lastly, activity was shown by certain azole derivaties of ferrocene which could potentially exist in a form featuring a cationic site. 25 As the clonogenic assay 21 revealed some activity even for the two non-oxidized but moderately water-soluble compounds, ferrocenylacetic acid and ferrocylthiomalic acid, whereas an equally non-oxidized but water-insoluble ferrocenyl-substituted cis-diaminedichloroplatinum(II) complex proved inactive, 26 we concluded 27,28 that it should be irrelevant whether a ferrocene compound be administered in the original (ferrocene) or in the oxidized (ferricenium) state, as long as the compound possessed sufficient water solubility to enter the vascular system rapidly. The 1/1 equilibrium distribution in any body compartment should, after all, be dictated in the first place by the compound's reduction potential and by such environmental conditions as pH or enzymic activity, rather than by the oxidation state in which the compound existed when originally administered.…”
mentioning
confidence: 99%
“…It was found that uncharged ferrocene conjugates of polyaspartatamides (in vitro) [12] and ferrocenylethyl benzimidazole (in vivo) [11] demonstrated the inhibition effect as well. Moreover, potentially anionogenic acids such as ferrocenylacetic FcCH 2 COOH and ferrocenylmethylthiomalic FcCH 2 S-CHCOOH-CH 2 COOH in clonogenic in vitro tests inhibited a formation of colonies of cells of human lung cancer and cultures of lung carcinoma PC-9, [6] to even a greater degree than do ferricenium salts. This effect does not develop immediately after incubation; a certain prolonged period is needed.…”
Section: Introductionmentioning
confidence: 99%
“…[4 -12] It can be assumed that the presence or possibility of acquisition of a positive charge is necessary for manifestation of the antitumor effects of ferrocene compounds. [6,13] Thus, positive-charged ferricenium salts with different substituents [3,4,8] -polyferrocenylenemethylene ologomer with ferrocene and ferricenium moieties, [8] bis-(ferrocenylmethyl)imidazolium salt [8] and bis-(ferrocenylalkyl) benzotriazolium salts [8] -in in vivo experiments inhibited tumor growth. It was found that uncharged ferrocene conjugates of polyaspartatamides (in vitro) [12] and ferrocenylethyl benzimidazole (in vivo) [11] demonstrated the inhibition effect as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation